2018
DOI: 10.1093/nar/gky060
|View full text |Cite
|
Sign up to set email alerts
|

Acute hepatotoxicity of 2′ fluoro-modified 5–10–5 gapmer phosphorothioate oligonucleotides in mice correlates with intracellular protein binding and the loss of DBHS proteins

Abstract: We reported previously that a 2′ fluoro-modified (2′ F) phosphorothioate (PS) antisense oligonucleotides (ASOs) with 5–10–5 gapmer configuration interacted with proteins from Drosophila behavior/human splicing (DBHS) family with higher affinity than PS-ASOs modified with 2′-O-(2-methoxyethyl) (2′ MOE) or 2′,4′-constrained 2′-O-ethyl (cEt) did. Rapid degradation of these proteins and cytotoxicity were observed in cells treated with 2′ F PS-ASO. Here, we report that 2′ F gapmer PS-ASOs of different sequences cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 48 publications
1
67
0
Order By: Relevance
“…For example, one kind of modication on phosphodiesters, phosphorothioate (PS), which is used in mipomersen and nusinersen, among others, could not only increase the nuclease resistance, but also enhance the intracellular internalization of ASOs, with the cytotoxicity of PS also determined in some of the cases. 2,3,[8][9][10] As in our previous reports, inserting an aminoalkyl side chain into the 4 0 -or 5 0 -site of nucleosides could signicantly increase the nuclease resistance of the resulting oligonucleotides. [11][12][13][14][15] Due to the decrease of nuclease resistance when the terminal amino moiety was protected by acetyl groups, it is assumed that the positive charge on the amino moiety of the aminoalkyl side chain acts as an obstacle to nucleases binding to oligonucleotides, and thus inhibits the degradation of oligonucleotides.…”
Section: Introductionmentioning
confidence: 63%
“…For example, one kind of modication on phosphodiesters, phosphorothioate (PS), which is used in mipomersen and nusinersen, among others, could not only increase the nuclease resistance, but also enhance the intracellular internalization of ASOs, with the cytotoxicity of PS also determined in some of the cases. 2,3,[8][9][10] As in our previous reports, inserting an aminoalkyl side chain into the 4 0 -or 5 0 -site of nucleosides could signicantly increase the nuclease resistance of the resulting oligonucleotides. [11][12][13][14][15] Due to the decrease of nuclease resistance when the terminal amino moiety was protected by acetyl groups, it is assumed that the positive charge on the amino moiety of the aminoalkyl side chain acts as an obstacle to nucleases binding to oligonucleotides, and thus inhibits the degradation of oligonucleotides.…”
Section: Introductionmentioning
confidence: 63%
“…No caspase activation was observed 506 in the absence of intranuclear inclusions, identifying nuclear inclusion as complicit in 507 caspase activated apoptosis, leading to cell death. The tumour suppressor protein p53 was 508 decreased, following transfection with 2´ O-methyl phosphorothioate AOs, relative to 509 untreated control cells (Figure 5b and c), suggesting that the cell death observed was p53 510 independent, contrary to the findings by Shen et al, 2018(Shen et al 2018) when using a 2′ 511 fluoro-modified AO on a phosphorothioate backbone in the mouse. In comparison to 512 phosphorothioate AO transfection, p53 levels remained unchanged following PMO 513 transfection (Figure 5b and c).…”
mentioning
confidence: 84%
“…Early work 85 indicated that negatively charged phosphorothioate AOs bind non-specifically to heparin-86 like proteins, laminin and collagen (Dias and Stein 2002) and more recently, 87 phosphorothioate AOs were reported to interact with nuclear paraspeckle-associated 88 proteins, sequestering them away from their endogenous target, the long non-coding RNA 89 NEAT1, and also seeding paraspeckle like-structures in the absence of NEAT1 (Shen et al 90 2014, Shen et al 2015). Paraspeckles and paraspeckle proteins are involved in 91 transcriptional regulation, transport and splicing pathways (Bond and Fox 2009, antisense oligonucleotides with a 5-10-5 gapmer configuration in mice (Shen et al 2018) 105…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sugar modifications to give a high affinity to nucleic acids cause increased off-target cleavage of ASOs and siRNAs [148][149][150]. This is because in this case, 1-2 mismatches are tolerable and hybridization can take place in shorter regions of homology [151]. Phosphorothioated oligonucleotides demonstrated pro-inflammatory properties [152].…”
Section: Challenges In Therapeutic Targeting Of Lncrnasmentioning
confidence: 99%